Kulturowe bariery skutecznego wdrożenia zarządzania wiedzą na przykładzie Gambit-Lubawka Sp. z o.o. - Tabaszewska, Edyta (The Culture Conditions of the Effective Implementation of the Knowledge Management for Gambit-Lubawka Ltd Example, 2006)
The aim of the paper is to present the results of questionnaire research concerning the organization culture in Gambit-Lubawka Ltd. The results of the research indicate the degree which the organization culture furthers the knowledge management - the conception which is implemented in the mentioned enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 519-525